PENGARUH EARNING PER SHARE DAN PRICE EARNING RATIO TERHADAP DEBT TO EQUITY RATIO DAN HARGA SAHAM PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Meida Dzulqodah, Yuniep Mujati S, (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2016)
abstractThe purpose of this study was to determine whether there is influence: 1) earning per share of the debt to equity ratio; 2) price earnings ratio of the debt to equity ratio; 3) earnings per share to the stock price; 4) price earnings ratio of the stock price; 5) debt to equity ratio to stock prices; 6) earnings per share to share prices through debt to equity ratio; 7) price earnings ratio of the stock price through a debt to equity ratio. The study design used is quantitative descriptive. Secondary data types, method of data collection through the documentation. The population used in this study is the enterprise data food and beverage sector in the Indonesia Stock Exchange (BEI) as many as 17 companies. The sampling technique purposive sampling method. Analysis of data to test the hypothesis in this study using path analysis (Path analys). Based on the analysis can be concluded that: 1) there is significant negative influences of the Earning Per Share (EPS) of the Debt to Equity Ratio (DER); 2) there is no significant positive effect of price earning ratio (PER) of the Debt to Equity Ratio (DER); 3) there is a significant negative influence Earning Per Share (EPS) to share price; 4) there is a significant positive effect Price Earning Ratio (PER) on stock prices; 5) there is a significant positive effect Debt to Equity Ratio (DER) on stock prices; 6) there is indirect influence Earning Per Share (EPS) to share price through the Debt to Equity Ratio (DER) and 7) There is an indirect effect Price Earning Ratio (PER) on stock prices through the Debt to Equity Ratio (DER).Keywords: Earning Per Share (EPS), Price Earning Ratio (PER), Debt to Equity Ratio (DER), the stock price abstrakTujuan dari penelitian ini adalah untuk mengetahui apakah terdapat pengaruh : 1) earning per share terhadap debt to equity ratio; 2) price earning ratio terhadap debt to equity ratio; 3) earning per share terhadap harga saham; 4) price earning ratio terhadap harga saham; 5) debt to equity ratio terhadap harga saham; 6) earning per share terhadap harga saham melalui debt to equity ratio; 7) price earning ratio terhadap harga saham melalui debt to equity ratio. Desain penelitian yang digunakan dalam penelitian ini adalah deskriptif kuantitatif. Jenis data sekunder, metode pengumpulan data melalui dokumentasi. Populasi yang digunakan dalam penelitian ini adalah data perusahaan sektor makanan dan minuman di Bursa Efek Indonesia (BEI) sebanyak 17 perusahaan. Teknik pengambilan sampel dengan metode purposive sampling. Analisis data untuk pengujian hipotesis pada penelitian ini menggunakan analisis jalur (Path Analys). Berdasarkan analisis dan pembahasan dapat disimpulkan bahwa: 1) terdapat pengaruh negatif signifikan Earning Per Share (EPS)  terhadap Debt to Equity Ratio (DER); 2)terdapat pengaruh positif tidak signifikan Price Earning Ratio (PER)  terhadap Debt to Equity Ratio (DER); 3) Terdapat pengaruh negatif signifikan Earning Per Share (EPS)  terhadap harga saham; 4) Terdapat pengaruh positif signifikan Price Earning Ratio (PER)  terhadap harga saham; 5) Terdapat pengaruh positif signifikan Debt to Equity Ratio (DER)  terhadap harga saham; 6) Terdapat pengaruh tidak langsung Earning Per Share (EPS) terhadap harga saham melalui Debt to Equity Ratio (DER)  dan 7) Terdapat pengaruh tidak langsung Price Earning Ratio (PER) terhadap harga saham melalui Debt to Equity Ratio (DER).Kata Kunci : Earning Per Share (EPS), Price Earning Ratio (PER), Debt to Equity Ratio (DER), harga sah